2013
DOI: 10.1155/2013/483832
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring and Elimination of Perfluorinated Compounds and Polychlorinated Biphenyls through Perspiration: Blood, Urine, and Sweat Study

Abstract: Perfluorinated compounds (PFCs) are man-made organofluorine chemicals manufactured and marketed for their stain-resistant properties. Polychlorinated biphenyls (PCBs) are anthropogenic organochlorine compounds previously used in various industrial and chemical applications prior to being banned in the Western world in the 1970s. Both PFCs and PCBs are persistent contaminants within the human organism and both have been linked to adverse health sequelae. Data is lacking on effective means to facilitate clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…In a series of studies, Genuis et al [311][312][313][316][317][318] measured the concentration of environmental toxicants in the blood, sweat, and urine of humans. The overall finding of these studies was that many chemicals, including persistent organic pollutants, heavy metals, bisphenol A (BPA), and phthalate are excreted in sweat.…”
Section: Excretion Of Toxicantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of studies, Genuis et al [311][312][313][316][317][318] measured the concentration of environmental toxicants in the blood, sweat, and urine of humans. The overall finding of these studies was that many chemicals, including persistent organic pollutants, heavy metals, bisphenol A (BPA), and phthalate are excreted in sweat.…”
Section: Excretion Of Toxicantsmentioning
confidence: 99%
“…First, many of these studies used sweat collection methods that are susceptible to surface contamination and sweat evaporation, which would artificially increase the concentration of toxicants measured in sweat samples. For instance, in most of these studies [311][312][313][314][316][317][318], sweat was collected by the subjects on their own (uncontrolled, unsupervised), from any site on their body, by scraping sweat from the skin surface with a stainless steel spatula into a glass jar. With these methods, it is probable that sweat samples were tainted with sebum secretions.…”
Section: Excretion Of Toxicantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, BPA and TCS have been detected in urine (Arbuckle et al, ; Philippat et al, ), amniotic fluid (Philippat et al, ; Shekhar et al, ), meconium and breast milk (Arbuckle et al, ), blood (Shekhar et al, ), hair (Lee, Kim, Kim, & Cho, ; Martín, Möder, Gaudl, Alonso, & Reemtsma, ) and nails (TCS) (Shi, Liu, Zhang, & Shao, ). PFOA has been also detected in a variety of biological samples such as amniotic fluid, blood, urine, breast milk and hair (Al‐sheyab, Al‐Qudah, & Tahboub, ; Alves, Jacobs, Vanermen, Covaci, & Voorspoels, ; Genuis, Beesoon, & Birkholz, ; Stein, Wolff, Calafat, Kato, & Engel, ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been minimal study on means to specifically facilitate removal of PFCs from the human body, and recent research exploring the potential elimination of these compounds through skin depuration demonstrated a lack of success [32]. Another potential approach is to give oral agents which reduce PFC absorption in the GI tract and/or increase toxicant excretion via blocking of reabsorption of toxics in the enterohepatic pathway.…”
Section: Introductionmentioning
confidence: 99%